Effect of Low Light on the Characteristics of Photosynthesis and Chlorophyll a Fluorescence During Leaf Development of Sweet Pepper - SUI, Xiao-lei; MAO, Sheng-li; WANG, Li-hao; ZHANG, Bao-xi; ZHANG, Zhen-xian (Journal of Integrative Agriculture, 2012)
Low light stress is one of the main limiting factors which influence the production of sweet pepper under protected cultivation in China. In this experiment, two genotypes of sweet pepper, ShY （low light-tolerant genotype） and 20078 （low light-sensitive genotype）, were used to study the effects of low light （photosynthetic photon flux density, PPFD was 75- 100 umol m-2 s-1, control 450-500 umol m-2 s-1） on photosynthesis during leaf development. The result indicated that under low light chlorophyll content, net photosynthetic rate （PN）, photosynthetic apparent quantum efficiency （Фi） and carboxylation efficiency （CE） of sweet pepper leaves increased gradually and decreased after reaching the maximum levels. The time to reach the peak values for all the above parameters was delayed, whereas the light compensation point （LCP） decreased gradually along with leaf expansion. The decrease in maximum quantum yield of PS II （Fv/Fm） was not observed at any stages of the leaf development under low light condition, but the actual PS II efficiency under irradiance （ФPS II） was lower accompanied by an increased non-photochemical quenching （NPQ） in young and/or old leaves compared with mature leaves. The antenna thermal dissipation （D） was a main way of heat dissipation when young leaves received excessive light energy, while the decline in photosynthetic function in senescence leaf was mostly owing to the decrease in carbon assimilation capacity, followed by a significantly increased allocation of excessive energy （Ex）. Compared with 20078, ShY could maintain higher PN, ФPS II and lower QA reduction state for a longer time during leaf development. Thus, in ShY photosynthetic efficiency and the activity of electron transport of PS II were not significantly affected due to low light stress.